Efficient Allocation of Indivisible Goods in Pseudomarkets with Constraints - Gul, Faruk; Pesendorfer, Wolfgang; Zhang, Mu (Journal of Political Economy, 2024)
We provide conditions under which a market mechanism can be used to allocate indivisible goods efficiently. We consider an economy with no transfers and show the existence and efficiency of Walrasian equilibria in the corresponding pseudomarket with stoch
Keywords: Market Mechanism; Pseudomarkets; Stochastic Consumption; Indivisible Goods